2022
DOI: 10.1002/hep.32719
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic paracrine signaling by cardiotrophin‐like cytokine factor 1 ameliorates diet‐induced NASH in mice

Abstract: Background and Aims: The mammalian liver harbors heterogeneous cell types that communicate via local paracrine signaling. Recent studies have delineated the transcriptomic landscape of the liver in NASH that provides insights into liver cell heterogeneity, intercellular crosstalk, and disease‐associated reprogramming. However, the nature of intrahepatic signaling and its role in NASH progression remain obscure. Approach and Results: Here, we performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Notably, other members of the IL-6 family, such as IL-6, CT1, CNTF, and LIF, have been confirmed to be involved in metabolic homeostasis, which exert antiobesity effects but mainly by acting on the central nervous system ( 11 16 ). Interestingly, a recent study showed that CLCF1 was a cholangiocyte-derived paracrine factor and played adaptive and protective roles during NASH pathogenesis ( 38 ). However, the role of CLCF1 in regulating metabolic homeostasis and whether CLCF1 could also target the central nervous system remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, other members of the IL-6 family, such as IL-6, CT1, CNTF, and LIF, have been confirmed to be involved in metabolic homeostasis, which exert antiobesity effects but mainly by acting on the central nervous system ( 11 16 ). Interestingly, a recent study showed that CLCF1 was a cholangiocyte-derived paracrine factor and played adaptive and protective roles during NASH pathogenesis ( 38 ). However, the role of CLCF1 in regulating metabolic homeostasis and whether CLCF1 could also target the central nervous system remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we identified CLCF1 as an adipocyte-derived cytokine and revealed that CLCF1 autocrine signaling was a pivotal suppressor of thermogenic capacity, thereby leading to metabolic disorders. In addition, a recent study revealed that CLCF1 was an intrahepatic cholangiocyte-derived secreted factor that was elevated in the liver in nonalcoholic steatohepatitis (NASH) patients, and it performed a protective role during NASH pathogenesis ( 45 ). According to our findings and those of others, CLCF1 expression is increased in both adipose tissues and the liver under metabolic stress conditions, but CLCF1 has an adverse effect on adipocyte thermogenesis and a favorable effect in hepatic metabolism, illustrating the complex role of CLCF1 in maintaining tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiotrophin-like cytokine factor 1 is another cholangiocyte-derived paracrine factor that exerts beneficial effects in NASH. Downregulation of a subunit of its receptor complex leukemia inhibitory factor receptor contributes to the progression of NASH[ 103 ]. Compared with other nonparenchymal cells, there are fewer studies addressing the effects of cholangiocytes on NASH, and a related therapeutic approach is still lacking.…”
Section: Approaches Targeting Lsecs and Cholangiocytes To Treat Nafldmentioning
confidence: 99%